2007
DOI: 10.1002/cm.20182
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a population of motile neurons in long‐term cortical culture

Abstract: The specific phenotypes and progression to maturity of primary cortical neurons in long-term culture correlate well with neurons in vivo. Utilizing a model of neuronal injury in long-term cultures at 21 days in vitro (DIV), we have identified a distinct population of neurons that translocate into the injury site. 5-bromo-2'-deoxyUridine (BrdU) incorporation studies demonstrated that neurons with the capacity to translocate were 21 days old. However, this motile ability is not consistent with the traditional vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Neuron cultures were prepared as reported previously (Dickson et al, 2000). This culture technique produces nerve cells that are relatively mature and reflective of the adult CNS (Chuckowree and Vickers, 2003;Chung and West, 2004;King et al, 2006;Haas et al, 2007). Briefly, neocortical tissue was removed from embryonic day (E)18 (sperm-positive day ¼ E1) Hooded Wistar rat embryos and incubated in sterile 10 mM HEPES buffer (378C).…”
Section: Cortical Cell Culturementioning
confidence: 99%
“…Neuron cultures were prepared as reported previously (Dickson et al, 2000). This culture technique produces nerve cells that are relatively mature and reflective of the adult CNS (Chuckowree and Vickers, 2003;Chung and West, 2004;King et al, 2006;Haas et al, 2007). Briefly, neocortical tissue was removed from embryonic day (E)18 (sperm-positive day ¼ E1) Hooded Wistar rat embryos and incubated in sterile 10 mM HEPES buffer (378C).…”
Section: Cortical Cell Culturementioning
confidence: 99%
“…While it has been shown that small populations of cultured neurons can migrate in response to specific stimuli, the large majority of cultured neurons are considered non-motile. 35,36 Conversely, astrocytes have been shown to migrate readily even in the absence of stimulation, 37 and therefore we would expect a higher ratio of non-confined astrocytes to neurons if post-seeding migration was dominant. This suggests that cell confinement may not be a critical factor if each chamber is seeded with cells from the same initial population, however in instances where two distinct cell populations are seeded in opposing chambers, reducing microchannel height to prevent cellular cross-contamination is critical.…”
Section: Resultsmentioning
confidence: 99%
“…We saw high levels of transgenic tau protein throughout neuritic projections in differentiated neurospheres from both human tau transgene genotypes. The presence of tau in the filopodia-spines of developing cells [74], [83] suggests that the phenomenon correlates with a dynamic morphology and does not necessarily indicate pathological injury.…”
Section: Discussionmentioning
confidence: 99%